RERANGKAINTEGRASI NILAIPELANGGAN DAN KINERJA MANAJEMEN HUBUNGAN PELANGGAN BERDASARKAN PERSEPSI PELANGGAN KORPORAT - Ellen Dwi Cahya; Siti Rahayu; Ema Andajani (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2010)
This research focuses on the influence of the dimensions of customer value to the customer satisfaction, brand loyalty, and customer behavior-based Customer Relationship Management performance; the influence of customer satisfaction on brand loyalty and customer behavior-based Customer Relationship Management performance; the influence of brand loyalty to customer behavior-based Customer Relationship Management performance. Based on samples taken the corporate customer Hotel Roditha Banjarmasin, then this research shows that customers value that includes emotional value, functional value has a significant impact on customer satisfaction, brand loyalty, and customer behavior-based Customer Relationship Management performance, while the other dimensions of customer value customer perceived sacrifices have no significant impact on customer satisfaction, brand loyalty, but the impact on customer behavior-based Customer Relationship Management performance and social values have a significant impact on customer satisfaction and brand loyalty; customer satisfaction has a significant impact on brand loyalty and customer behavior-based Customer Relationship Management performance ; and brand loyalty has a significant impact on customer behavior-based Customer Relationship Management performance